South China Sea : promise and problems of COC - Vu, Truong-Minh (2014)
Since the escalation of tension in the South China Sea in early 2014, establishing a code of conduct(COC) has become more pressing. Foreign ministers from China and ASEAN who met in Naypyitaw last weekend agreed to speed up hammering out a legally-binding COC. Can there be an early conclusion of the COC?